Total Nitrogen in forage corn (Zea mays L.) estimated by satellite Sentinel-2 spectral indices - López-Calderón, Magali J.; Estrada-Ávalos, Juan; Martínez-Sifuentes, Aldo R.; Trucíos-Caciano, Ramón; Miguel-Valle, Enrique (REVISTA TERRA LATINOAMERICANA, 2023)
Nitrogen is the most important nutrient for forage crops because of its contribution in various biochemical reactions in the dif ferent phenological stages of the plant. The main aim of this study is to develop a multiple linear regression model to estimate total nitrogen (Nt) in corn plants using spectral indexes. The percentage of total nitrogen (Nt) was determined through three plant samplings in four experimental plots. The estimation model was obtained to process the Sentinel-2 satellite images according to the plant sampling dates; 13 spectral indexes were calculated and the association between nitrogen and the reflectance values was analyzed by the principal component analysis (ACP), correlation matrix, and dendrogram. The indexes with the highest relationship were MCARI / OSAVI, TCARI / OSAVI, MCARI / OSAVI RE and TCARI / OSAVI RE, explaining more than 50% of the variability of the proposed model and a MSE of 0.12. This study indicates that the estimation obtained from Sentinel-2 spectral indexes images has great potential to determine nitrogen in crops. However, for future research, Nt estimation models should be obtained for each phenological crop stage.